The association between gut microbiota-derived metabolites and arterial stiffness in hypertensive patients. - Ibragimova, Feruza; Kalenderova, Guljakhan; Kalmuratova, Bibigul; Okhunova, Munojoat; Kholmuradova, Zilola; Ikramova, Feruza; Axmedov, Nodir (Revista Latinoamericana de Hipertensión, 2025)
The present study aimed at investigating the association of gut microbial metabolites with arterial stiffness in patients with hypertension. This cross-sectional study was conducted on 120 hypertensive patients attending Tashkent clinics. Assessments included measurement of plasma levels of TMAO metabolites and SCFAs, arterial stiffness measured by the carotid-femoral pulse wave velocity method, and analysis of the microbiota composition. The study results indicated that TMAO levels were positively and significantly associated with the cf-PWV index, with a correlation coefficient of 0.48 (p < 0.001). On the other hand, butyrate was negatively associated with cf-PWV, with a correlation coefficient of -0.42 (p < 0.001). Multiple regression analysis presented both metabolites to be independently associated with arterial stiffness: the beta coefficient for TMAO was 0.35 and for butyrate was -0.28. When comparing different metabolic quartiles, the levels of cf-PWV were significantly higher for those patients with high TMAO levels: 11.2 vs. 8.5 m/s (p < 0.001). Moreover, microbiological analyses showed that richness in particular bacterial genera was significantly associated with metabolite levels. The results from this study confirm that gut microbial metabolites play an independent role in the pathophysiology of arterial stiffness and may provide novel strategies for risk assessment and therapeutic interventions in patients with hypertension.